Biaya perjalanan domestik pengunjung terhadap manfaat rekreasi di taman wisata alam punti kayu (TWAPK) kota Palembang - Rommy Qurniati; Abdur Rahman Saleh (Institut Pertanian Bogor, 2010)
Punti Kayu Nature Park can provide various benefits. Currently benefits obtained are still considering to be low. An objective and quantitative assessment of a recreation benefits by calculated travel cost and willingness to pay of visitors to recreation benefits, in the end good for as consideration to determine development alternative, construction and cost of conservation activity in Nature Park Punti Kayu (TWAPK). This research was conducted in the Nature Park Punti Kayu Palembang city, South Sumatra Province. The object of research in this study were the respondents (visitors) in the Nature Park Punti Kayu. Number of visitors samples in this study were 100 visitors. Data obtained in the form of tabulations and percentages, then analyzed descriptively. According to the research, visitor assessment to TWAPK related to condition of road to recreation object, accessibility, biodiversity, and recreation facility are good with mean score 3,62, 3,91, 3,18,and 3,33. While security and information service are ugly, with mean score 2,58. Mean of travel cost of visitor TW APK range from Rp 44.913,04 till Rp172.000,00. Progressively far the distance which is gone through by a visitor from home to location of recreation, hence expend more and more traveling cost conversely. Totalize value of willingness to pay of visitors in TWAPK for forest and land cost rehabilitation equal to Rp 876.070.734,00/year.